Trastuzumab emtansine of the treatment of HER2-positive breast cancer with brain metatases - L. Yu. Vladimirova; I. L. Popova; N. A. Abramova; M. A. Teplyakova; N. M. Tikhanovskaya; K. A. Novoselova; A. A. Lyanova; L. A. Ryadinskaya; M. O. Ezhova; V. S. Myagkova; L. K. Strakhova (Медицинский совет, 2020)
Patients with brain metastases of HER2-positive breast cancer (BC) is a special group of patients who are difficult to treat and have a short life expectancy. The possibilities of whole brain radiotherapy, stereotactic radiosurgery and surgery in such patients are rather limited. Trastuzumab emtansine (T-DM1) showed potential activity in this subset of patients. T-DM1 is an antibody-chemical conjugate (ADC) that delivers directly to HER2-positive cancer cells, thereby limiting damage to healthy tissue. At this point, the efficacy of trastuzumab emtansine has been demonstrated in several randomized trials as a second and subsequent lines of therapy for advanced breast cancer with a favorable toxicity profile of the drug. This article describes a clinical case of a patient with luminal B HER-2 positive breast cancer who, underwent stereotactic radiosurgery and was treated with trastuzumab emtansine as a the second line of treatment for disease progression with metastatic brain lesions after trastuzumab/pertuzumab-containing therapy. Partial regression of metastases with long-term duration of the effect was achieved treatment with trastuzumab emtazine has been being continued for 24 months. Tolerability of therapy was good: thrombocytopenia 2 degree was the main among side effects. The effect has been persisted for 2 years and the patient continues the treatment. Discussion of the results of real clinical practice with well-known studies was carried out.